DAMPAK DIMENSI SERVQUAL TERHADAP KEPUASAN PASIEN, KOMUNIKASI WORD OF MOUTH, DAN REPURCHASE INTENTIONS PADA RUMAH SAKIT SWASTA DIKOTA PADANG - Haryeni, Haryeni; Yendra, Nofri (LPPM Universitas Muhammadiyah Sumatera Barat, 2020)
This study aims to determine: Effect of Servqual Dimension (Responsiveness) on Patient Satisfaction, Effect of Servqual Dimension on Patient Satisfaction, Effect of Servqual Dimension (Assurance) on Patient Satisfaction, Effect of Servqual Dimension (Reliability) affect on Patient Satisfaction, Effect of Servqual Dimension (Tangible) influence on Patient Satisfaction, Effect of Patient Satisfaction on Repurchase Intentions, Effect of Patient Satisfaction on WOM Communication, Effect of WOM Communication on Repurchase Intentions. The population in this study is the population of the city of Padang /consumers who has been used services at three Private Hospitals in the city of Padang, namely the Citra Bunda Public Hospital Medical Center, Ibnu Sina Islamic General Hospital and Siti Rahmah Hospital. The number of research samples used were 138 respondents. Sampling technique using accidental sampling. The data analysis technique used in testing the hypothesis of this study is SEM analysis using the Partial Least Square (PLS) program. The results showed that Assurance had a significant effect on Satisfaction, Empathy had no significant effect on Satisfaction, Reliable had no significant effect on Satisfaction, Responsibility had a significant effect on Satisfaction, Tangible had no significant effect on Satisfaction, Satisfaction had a significant effect on Repurchase Intentions, Satisfaction had no significant effect on Communication WOM, WOM communication has no significant effect on Repurchase intentions. The R-square value of the Servqual dimension variable has an effect on Satisfaction of 53.3%, the satisfaction variable has an effect on the repurchase intentions variable of 53.9% and the Repurchase Intentions variable has an effect on the WOM Communication of 41.4%. Keywords: ServQual, Patient Satisfaction, Repurchase Intentions, WOM Communication